Studi Literatur Pengembangan E-LKPD Mata Pelajaran Kimia Di SMA - Sonny Rohimat; R.A Annita Meilina A; Anita Siallagan (Prosiding Temu Ilmiah Nasional Guru, 2022)
One of the plans that must be carried out by teachers in learning activities is the preparation of learning tools, including student worksheets. Along with the rapid development of information and communication technology, many student worksheets are developed electronically known as E-LKPD. This research aims to analyze the development of E-LKPD of Chemistry subject at the senior high school. This research was conducted through a literature study of articles that have been published through Indonesian-language proceedings or journals indexed by Google Scholar. The results of the study of these articles were analyzed descriptively on four main focuses, namely the orientation of developing E-LKPD; the purpose of developing E-LKPD; the development model used; application or platform used in the development of E-LKPD. Based on the results of the study, it is known that the orientation of the development of E-LKPD is a learning model, learning approach, or learning outcomes; aims to improve student learning outcomes in the realm of attitudes or knowledge; using ADDIE, 4D, Kemp, or Plomp models; by using several applications or platforms.